Innovation Policy of the European Union – Overview of Theoretical Foundations and Empirical Aspects - Wysokińska , Zofia (Journal of Vasyl Stefanyk Precarpathian National University, 2017)
The aim of this article is to analyse the directions and instruments of the innovation policy of the European Union, showing how its theoretical and structural underpinnings influence innovation, which is considered one of the main factors in enhancing the competitiveness of both enterprises and countries on the international market. The article also analyses how technology transfers and knowledge exchanges (spillovers) influence changes in international competiveness at both the micro- and macro-economic levels, as well as the significance of the internationalization of enterprises resulting from Foreign Direct Investment (FDI) in terms of the diffusion of innovative processes at both the European and international levels. In this regard special attention is given to the financing of R&D in the successive Framework Programmes of the European Union aimed at supporting innovation